2015
DOI: 10.26428/1606-9919-2015-182-269-276
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical effect of low-molecular peptides in extracts and hydrolyzates from tissues of water organisms

Abstract: Molecular-weight composition of peptides in extracts and hydrolyzates from soft tissues of the clams Corbicula japonica and Mercenaria mercenaria and liver of chum salmon is investigated. Antiradical activity is defined for low-molecular peptides, as well as for high-molecular proteins and free amino acids in the extracts. The maximum activity is detected for the extracts of salmon liver; all protein fractions in the water extract of the liver have antiradical activity. Low-molecular peptides and free amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…According to the literature and our own data, protein hydrolysates have a higher ARP than pure protein preparations. For example, it has been previously shown that the reducing ability of proteins increases with the degradation of the molecular weight of the protein [ 26 , 28 ]. In other words, the ARP of the native protein is less (with a reservation about some enzymes) than that of the hydrolysis products of its molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature and our own data, protein hydrolysates have a higher ARP than pure protein preparations. For example, it has been previously shown that the reducing ability of proteins increases with the degradation of the molecular weight of the protein [ 26 , 28 ]. In other words, the ARP of the native protein is less (with a reservation about some enzymes) than that of the hydrolysis products of its molecule.…”
Section: Resultsmentioning
confidence: 99%
“…For example, whey protein hydrolyzate is 9.5–10 times more active than wheat gluten protein from bakery products made from premium flour. We attribute this both to an increase in the spatial availability of the amino acid side chains of polypeptides and to an increase in the concentration of C- and N-terminal fragments of polypeptides per volume of reacting mixtures [ 12 , 28 ]. With some exceptions, all studied samples are distributed in the following order according to the increase in their activity: native proteins < less protein-enriched hydrolysates < more protein-enriched hydrolysates < a mixture of molecular amino acids.…”
Section: Resultsmentioning
confidence: 99%